The Correlation between Body Mass Index and Lifting Frequency with Low Back Pain Complaints on Rice Transport Workers in Warehouse of Perum BULOG Subdivre Pematangsiantar - Ita Riyana Limbong1 , Noeroel Widajati2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Rice transport workers are at risk for Low Back Pain (LBP) complaints because their workis lifting heavy loads repeatedly and affected by individual characteristics. This research aimed to analyzethe strength of the correlation between body mass index and lifting frequency with LBP complaints on ricetransport workers in Perum BULOG Pematangsiantar Subdivre.Methods: This type of research was an observational research with a cross sectional design. The samplingtechnique used total populated sampling with 30 respondents. The variables researched included body massindex, lifting frequency, and LBP complaints.Data were collected by observation, filling out research questionnaires, and Nordic Body Map (NBM). Thedata analysis used was the Spearman correlation.Results: The strength of the correlation between body mass index with low back pain complaints had a valueof r = 0.203, the strength of the correlation between the lifting frequency with low back pain complaints hada value of r = 0.415.Conclusion: Body mass index with LBP complaints had a weak and positive correlation. The liftingfrequency with LBP complaints had a moderate and positive corelation.